Pelatihan dan Pengembangan Manajemen Sumber Daya Manusia dalam Efektifitas Organisasi Pemuda Persis Kabupaten Bandung Barat - Muhammad Rasyid, Naufal; Yuliani, Yuliani; Rahman, Arif (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to examine: (1) the planning of human resource, training and development at the Regional Leadership of Pemuda Persatuan Islam in West Bandung Regency, (2) the training and development process in management for organizational effectiveness, and (3) the outcomes of its implementation. A descriptive qualitative method was used with the POAC approach. The findings reveal that: (1) training and development were planned based on the need to address staff shortages, (2) the training process was carried out through on-the-job training aligned with members’ duties and roles, and (3) the implementation contributed to enhancing organizational effectiveness, particularly in strengthening Islamic preaching (da'wah) values within both the community and the organization.